2011
DOI: 10.1111/j.1476-5381.2011.01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific PEGylation of exenatide analogues markedly improved their glucoregulatory activity

Abstract: BACKGROUND AND PURPOSEExenatide is a 39-amino-acid peptide widely used to manage type 2 diabetes mellitus. However, it has a short plasma half-life and requires a twice daily injection regime. To overcome these drawbacks we used maleimide-polyethylene glycol to induce site-specific PEGylation. EXPERIMENTAL APPROACHThe analogue PB-105 (ExC39) was produced by replacing cysteine at position 39 of exenatide to provide a free thiol group. PB-105 showed the same glucoregulatory activity as exenatide in mice. Site-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…However, the half‐life of GLP‐1 in vivo is short, and it is rapidly degraded to GLP‐1(9‐36)amide by DPPIV (Deacon et al ., 1995; Knudsen and Pridal, 1996; Hansen et al ., 1999), and hence, there are continuing attempts to find long‐lasting peptide agonists with glucoregulatory properties (e.g. Gong et al ., 2011). Indeed, current therapeutic approaches have utilized DPPIV‐resistant mimetics of GLP‐1, most notably exenatide (Iltz et al ., 2006) and liraglutide (Neumiller and Campbell, 2009), both of which are in current therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…However, the half‐life of GLP‐1 in vivo is short, and it is rapidly degraded to GLP‐1(9‐36)amide by DPPIV (Deacon et al ., 1995; Knudsen and Pridal, 1996; Hansen et al ., 1999), and hence, there are continuing attempts to find long‐lasting peptide agonists with glucoregulatory properties (e.g. Gong et al ., 2011). Indeed, current therapeutic approaches have utilized DPPIV‐resistant mimetics of GLP‐1, most notably exenatide (Iltz et al ., 2006) and liraglutide (Neumiller and Campbell, 2009), both of which are in current therapeutic use.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous investigations have reported a deterioration of target potency with increasing PEG mass (Gong et al , ; Bianchi et al , ; Qiu et al , ), which is thought to originate from PEG‐chain length‐dependent altered steric shielding (Mu et al , ). We found that PEGylation of hPP on lysine side‐chains at positions 22 and 30 using different precursor peptides (hPP 2–36 and [Q 34 ]hPP) also induced significant reductions in activity that correlated mostly with PEG size.…”
Section: Discussionmentioning
confidence: 98%
“…In agreement with these results, we showed that female rats reduced GLP-1 hormone expression after the Zymosan injection. It was reported that GLP-1 hormone had an antinociceptive effect in formalin injected male rats [11,24]. This effect was related with the modulation of opioidergic system [25].…”
Section: Discussionmentioning
confidence: 99%